DETERMINATION OF URANIUM CONCENTRATION IN TEETH FEMALE SAMPLES USING FISSION TRACKS IN CR-39 FROM DIFFERENT COUNTRIES. - Hummadi, Sallama S (Al-Nahrain Journal of Science, 2010)
The present study was under taken to measure the uranium concentration in female teethsamples collected from different nationalities. The determination of uranium concentration in thesesamples has been done by using CR-39 track detector. The nuclear reaction is used as a source ofnuclear fission fragments is (n,f) obtained by the bombardment of U-235 with thermal neutronswith flux (5x103 n/cm2.s) was used from ( Am-Be) neutron source. The concentration values werecalculated by a comparison with standard samples which prepared. The obtained results show thatthe concentration is ranging from (0.58 0.7ppm) in Oman and Uae to (0.35 0.03ppm) in Iraqifor male, the uranium concentration was the highest in Oman and Uae for female.